Computational intelligence in wireless sensor networks : recent advances and future challenges - Abraham, Ajith, 1968-; Falcon, Rafael, 1979-; Koeppen, Mario (Springer, 2017)
This book emphasizes the increasingly important role that Computational Intelligence (CI) methods are playing in solving a myriad of entangled Wireless Sensor Networks (WSN) related problems. The book serves as a guide for surveying several state-of-the-art WSN scenarios in which CI approaches have been employed. The reader finds in this book how CI has contributed to solve a wide range of challenging problems, ranging from balancing the cost and accuracy of heterogeneous sensor deployments to recovering from real-time sensor failures to detecting attacks launched by malicious sensor nodes and enacting CI-based security schemes. Network managers, industry experts, academicians and practitioners alike (mostly in computer engineering, computer science or applied mathematics) benefit from the spectrum of successful applications reported in this book. Senior undergraduate or graduate students may discover in this book some problems well suited for their own research endeavors. USP: Presents recent advances and future challenges of computational intelligence (CI) in wireless sensor networks Surveys the state of the art in CI applied to challenging real-world problems in the wireless sensor networks realm Is useful for researchers, network managers, industry experts, academicians, and practitioners who all benefit from the wide spectrum of successful application domains.
Keywords: Computational intelligence.; Wireless sensor networks.; elektronické knihy; electronic books